2011
DOI: 10.1007/s00425-011-1397-9
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and expression of flowering-related genes under long-day conditions with light-emitting diodes

Abstract: The effects of light quality on flowering time were investigated in Gypsophila paniculata, which is a long-day cut flower, and with Arabidopsis under long-day conditions with light-emitting diodes (LEDs). Gypsophila paniculata plants were grown under natural daylight and flowering was controlled by long-day treatment with a weak LED light of a single color in the night. Flowering was promoted not by blue light, but by far-red light in G. paniculata, while flowering was promoted by both light colors in Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Ooi et al (2016) reported that the leaf length and area of the first two leaf pairs of Arabidopsis grown under a combination of red and blue laser light were higher than the control plants grown under white fluorescent light and equal or lower in the subsequent leaf pairs. Bolting and flowering times of red and blue laser grown plants were slightly delayed, which is most likely due to the absence of far-red light that promotes flowering (Ishiguri and Oda, 1972; Runkle and Heins, 2001). Although far-red as well as green light is photosynthetically inefficient, they exhibit some effects on the growth and development, especially in vegetative development, flowering, stomatal opening, and stem growth modulation (Folta and Maruhnich, 2007; Wang and Wang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ooi et al (2016) reported that the leaf length and area of the first two leaf pairs of Arabidopsis grown under a combination of red and blue laser light were higher than the control plants grown under white fluorescent light and equal or lower in the subsequent leaf pairs. Bolting and flowering times of red and blue laser grown plants were slightly delayed, which is most likely due to the absence of far-red light that promotes flowering (Ishiguri and Oda, 1972; Runkle and Heins, 2001). Although far-red as well as green light is photosynthetically inefficient, they exhibit some effects on the growth and development, especially in vegetative development, flowering, stomatal opening, and stem growth modulation (Folta and Maruhnich, 2007; Wang and Wang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a certain level of R is necessary for effective promotion of flowering. FR of a single color does not induce FT and FT homolog gene expression in Arabidopsis and G. paniculata, while SOC1 and SOC1 homolog gene expression is induced by FR of a single color and promotes flowering (Hori et al, 2011). Because, in contrast to FR, FR with both R and B (FR:R:B = 6 : 3 : 1) enhances FT homolog gene expression (Hori et al, 2011), the promotion of flowering by FR supplemented with R could be related to the enhancement of FT homolog gene expression in addition to SOC1 homolog expression in G. paniculata.…”
Section: Discussionmentioning
confidence: 90%
“…paniculata does not flower under long-day conditions with B, whereas Arabidopsis flowers early under B as well as under FR (Hori et al, 2011). The number of flowering or budding flower shoots per plant was similar between FR:B and FR (Tables 3 and 4) and between FR and FR:R:B-c, the ratios of B and R in the latter were the same and lower than those in FR:R:B-b, respectively; therefore, obvious promotion of flowering and flower budding was not found under B supplementation in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After removing genomic DNA from the RNA sample, quantitative reverse transcription (RT)-PCR was performed using the method of Hori et al (2011) and Nishio et al (2010) -movement-related genes in the tomato in the SOL genomics network (https:// solgenomics.net/) on the basis of annotations of ITAG2.3 made by the International Tomato Annotation Group (ITAG) (Bombarely et al, 2011;The Tomato Genome Consortium, 2012). The gene-specific primer sets were designed using Primer 3 (http://primer3.…”
Section: +mentioning
confidence: 99%